Peningkatan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Make A Match Berbantuan Media Kantong Perkalian pada Siswa Kelas II SDN 23 Ampenan - Dianah, Julia Hilalatud; Amrullah; Triapuri, Ade Hegar (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to examine the improvement of second-grade students’ mathematics learning outcomes on the topic of multiplication as repeated addition through the use of the Make a Match learning model supported by multiplication pocket media. The research was conducted in two cycles in Grade II of SDN 23 Ampenan during the Field Experience Practice (PPL) in the second semester of the 2023/2024 academic year. This classroom action research involved 27 students as research subjects. The data collected consisted of students’ learning outcomes and observation data related to student and teacher activities during the learning process. Data collection techniques included tests, observations, and documentation. The results show that the implementation of the Make a Match model assisted by multiplication pocket media in mathematics lessons successfully improved the learning outcomes of second-grade students at SDN 23 Ampenan. Prior to the intervention, the mastery percentage was only 33.33%. In Cycle I, it increased to 59.26%, and in Cycle II, it further improved to 85.19% of students achieving mastery.